2011
DOI: 10.1038/gene.2011.74
|View full text |Cite
|
Sign up to set email alerts
|

A whole genome methylation analysis of systemic lupus erythematosus: hypomethylation of the IL10 and IL1R2 promoters is associated with disease activity

Abstract: The etiology of systemic lupus erythematosus (SLE) involves a complex interaction of genetic and environmental factors. Investigations have shown that environmentally driven epigenetic changes contribute to the etiology of SLE. Here, we hypothesize that aberrant DNA methylation may contribute to the activation of the immune machinery and trigger lupus disease activity. A whole genome methylation array was applied to investigate the DNA methylation changes between 12 pairs of active SLE patients and healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 34 publications
(26 reference statements)
3
55
0
1
Order By: Relevance
“…For instance, the hypomethylation of the IL1R2 gene serves as a potential biomarker of autoimmune disease (51), and reduced IL1R2 expression is observed in atherosclerotic lesions compared with normal arteries (52). To our knowledge, this study is the first to report that intracellular IL1R2 is associated with angiogenesis of human CRC.…”
Section: Discussionmentioning
confidence: 73%
“…For instance, the hypomethylation of the IL1R2 gene serves as a potential biomarker of autoimmune disease (51), and reduced IL1R2 expression is observed in atherosclerotic lesions compared with normal arteries (52). To our knowledge, this study is the first to report that intracellular IL1R2 is associated with angiogenesis of human CRC.…”
Section: Discussionmentioning
confidence: 73%
“…To date, comparison of the divergence of DNA methylation in whole blood between cases and controls of common diseases has been well documented (Nadeau et al, 2010;Chowdhury et al, 2011;Toperoff et al, 2011;Lin et al, 2012). However, whole blood consists of many functionally and developmentally distinct cell populations in varying proportions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using animal models demonstrated that IL-1 is involved in the development of RA (18,19), and blockade of IL-1 signaling is effective in treating RA (20)(21)(22)(23), although this cytokine is primarily important in the development of autoinflammatory diseases, such as Familial Mediterranean fever, cryopyrin-associated periodic syndromesa, and Still's disease (19,24,25). Because the concentration of IL-1R2 protein is increased in the synovial fluid (26) and plasma (27,28) of RA patients, and the promoter region of the IL1R2 gene is hypomethylated in PBMCs of RA patients (28), IL-1R2 is suggested to be involved in its pathogenesis.…”
mentioning
confidence: 99%